2019
DOI: 10.1248/bpb.b19-00031
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Renal Efflux Transporter MATE1 in Renal Excretion of Flecainide

Abstract: Flecainide, an anti-arrhythmic drug, undergoes renal excretion through active renal tubular secretion in addition to passive glomerular filtration. The contribution of renal uptake and efflux transporters in active renal tubular secretion of flecainide remains unclear except that flecainide is a substrate of human multidrug resistance protein 1 (MDR1). To elucidate renal efflux and uptake transporters involved with active renal tubular secretion of flecainide, we conducted in vitro interaction studies of fleca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Test articles as inhibitors of transporters. Inside-out membrane vesicles prepared from HEK293 cells overexpressing a single transporter (vesicular transport inhibition assay) or cell lines (HEK293 and MDCKII) stably expressing a single transporter (uptake transporter inhibition) were used to determine the inhibitory effects of each test article on the designated transporter as described [21][22][23] using established probe substrates and inhibitors (Table S4). Each alkaloid was tested at 10 and 100 µM, whereas the goldenseal extract, standardized to berberine concentrations (detailed above), was tested at 1.75 µM and 17.5 µM (based on solubility limits).…”
Section: In Vitro Transporter Inhibition Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Test articles as inhibitors of transporters. Inside-out membrane vesicles prepared from HEK293 cells overexpressing a single transporter (vesicular transport inhibition assay) or cell lines (HEK293 and MDCKII) stably expressing a single transporter (uptake transporter inhibition) were used to determine the inhibitory effects of each test article on the designated transporter as described [21][22][23] using established probe substrates and inhibitors (Table S4). Each alkaloid was tested at 10 and 100 µM, whereas the goldenseal extract, standardized to berberine concentrations (detailed above), was tested at 1.75 µM and 17.5 µM (based on solubility limits).…”
Section: In Vitro Transporter Inhibition Assaysmentioning
confidence: 99%
“…Participants who completed the study self-identified as white (7 men and 6 women) or Asian (1 man and 2 women). The median (range) age was 27 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) and 26 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) for men and women, respectively. None of the participants reported taking concomitant medications or NPs known to modulate the metabolism of midazolam and disposition of the remaining probe drugs.…”
Section: Clinical Studymentioning
confidence: 99%
“…A excreção renal de medicamentos é um processo dinâmico e pode ser afetada por diversos fatores, como a função renal, o pH urinário, o fluxo sanguíneo renal, a idade e o sexo do paciente. Alterações na função renal podem ter um impacto significativo na excreção de medicamentos, podendo resultar em acúmulos tóxicos ou em níveis subterapêuticos no sangue (DOKI et al, 2019).…”
Section: Excreção Renalunclassified